Election, political instability and fragile democracy in Bangladesh: Is proportional representation the remedy? - Quddus, S. M. Abdul (Bangladesh Institute of Islamic Thought, 2014)

(untitled)
Being one of the most populous countries in the world, Bangladesh has been facing numerous challenges such as poverty, rampant corruption, decay in living conditions, slow economic growth, bad governance, insecurity and of course political conflicts and instability, which are supposed to be met in a democratic polity. After the fall of Ershad‘s military regime in 1990, democracy has been reinstated in the country. But the ―winnertakes-all political culture and mentality of the political elites has resulted in the boycott of parliament by the opposition parties followed by street agitations and general strikes on a regular basis. Thus many scholars argue that democracy in Bangladesh is not working as per the hope and aspiration of the people of Bangladesh. This paper examines the question of whether the Proportional Representation (PR) system can help in institutionalising and strengthening democratic practice in order to achieve political stability and sustained economic growth in Bangladesh. Our findings reveal that there is a need for political reforms, and particularly change from the existing ―Winner-Takes-All (WTA)‖ political system to the PR system in Bangladesh. This is because PR system paves the way for greater participation i.e. seats in the parliament are allocated among parties in proportion to votes they receive. Our data also shows that the PR system will not only grant legitimacy to the party with majority seats in the parliament to rule, but also build stakes for opposition parties to meaningfully participate in parliament by means of committee assignments in proportion to their representation i.e. the percentages of electoral votes and parliamentary seats. This paper further highlightes that the PR political system, which some scholars name it as a system with ‗justice as fairness principle‖, will also help to build a national consensus to resolve the issues of long-standing political contentious in Bangladesh such as appropriate electoral system, institutional framework of the electoral process, political neutrality of the Election Commission (EC), organise open, free and fair election, etc. These are some major political issues which are unresolved in the country for a long time and the PR system may bring a positive change in this respect by transforming traditional behavior of political elites thus making a difference in the quality of life of the citizenry in Bangladesh. The findings of this study also suggest that in order to adopt the PR system in a new democracy like Bangladesh there are also numerous challenges such as: commodification of election, commercialisation of nomination, the issue of geographical representation, instability of the government, etc.